PENGEMBANGAN MATA KULIAH HADIS TARBAWI PADA PERGURUAN TINGGI ISLAM - M Zuhri Abu Nawas; Sapruddin Sapruddin (LP2M IAIN Palangka Raya, 2020)
The Tarbawi Hadith material development is a study carried out in the framework of development and component results and approach analysis. This included the development of tarbawi hadith course accessed by integrating and interconnecting science. This research provided inspiration and innovation in the development of constructive scientific quality and presenting reinforcement of learning formulation material as a scientific study program. This study applied an exploratory-descriptive research designed qualitatively. The development of the Tarbawi hadith material required systemic steps and applied by maximizing the sustainable aspect of inter-connectivity between the basic structured of allied subject matter for the aspects of material functions and the methodology of the study of hadith material related to the contemporary religious studies.